2015
DOI: 10.1002/etc.3169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbicide dicamba on nontarget plants and pollinator visitation

Abstract: Nearly 80% of all pesticides applied to row crops are herbicides, and these applications pose potentially significant ecotoxicological risks to nontarget plants and associated pollinators. In response to the widespread occurrence of weed species resistant to glyphosate, biotechnology companies have developed crops resistant to the synthetic-auxin herbicides dicamba and 2,4-dichlorophenoxyacetic acid (2,4-D); and once commercialized, adoption of these crops is likely to change herbicide-use patterns. Despite cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 57 publications
2
77
0
4
Order By: Relevance
“…; Hanley & Wilkins ; Bohnenblust et al . ). Moreover, some herbicides can be directly toxic to larval stages of pollinators (Hahn et al .…”
Section: Insecticides and Herbicidesmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hanley & Wilkins ; Bohnenblust et al . ). Moreover, some herbicides can be directly toxic to larval stages of pollinators (Hahn et al .…”
Section: Insecticides and Herbicidesmentioning
confidence: 97%
“…; Bohnenblust et al . ). Their widespread and expanding cultivation could represent a threat to pollinators, increase pollination deficits and yield reduction in insect‐dependent crops, but this needs further study.…”
Section: Insecticides and Herbicidesmentioning
confidence: 97%
“…Finally there is some information indicating that the growth stage at which the plant is exposed may play an important role (e.g., Boutin and Rogers ; Gilreath and Chase ; Gilreath et al ; Strandberg et al ; Griffin et al ). For our separate investigation of the effect the application timing may have on the sensitivity, see Supplemental Data H, which also includes data from Bohnenblust et al (), Nelemans et al (), and Olszyk et al ().…”
Section: Resultsmentioning
confidence: 99%
“…The herbicide effects on reproduction were associated with reduced occurrence in plots and biomass for some species . Another example of field research was by Bohnenblust et al , who reported that 0.01× f.a.r. of dicamba reduced the number of flowers in Medicago sativa L. grown in field plots and Eupatorium perfoliatum L. grown in pots.…”
Section: Discussionmentioning
confidence: 99%